Majas Perbandingan dalam Buku Besar Peminum Kopi Karya Andrea Hirata dan Implikasinya terhadap Pembelajaran Teks Novel - Yelva Nofrianis; Zulfikarni Zulfikarni (Universitas Negeri Padang, 2022)
The use of figure of speech in literary works aims to obtain the effects of beauty and to convey the intent of the author. This study aims to describe the comparative figure of speech contained in Andrea Hirata's novel Buku Besar Peminum Kopi and to describe the comparative figure of speech in Indonesian language learning, namely the text of the XII high school novel. This type of research is a qualitative research using descriptive method. The data in this study are in the form of words, phrases, clauses, and sentences containing comparative comparisons in the novel Buku Besar Peminum Kopi by Andrea Hirata. The data source in this research is the novel Buku Besar Peminum Kopi by Andrea Hirata. Based on the research that has been done, it is found that comparative figure of speech consists of simile, metaphor, personification, antithesis, pleonasm, periphrasis, and also prolepsis or anticipation. The most dominant figure of speech used is metaphorical figure of speech with twenty two quotations. This is because Andrea Hirata dominantly uses figurative language explicitly in the novel. The least found figure of speech is the figure of speech periphrasis which is quoted one quote. This research can be implied in the form of a one-sheet Learning Implementation Plan (RPP) for class XII high school students at KD 3.9 and 4.9.